Study on gene action, heterosis and inbreeding depression for yield and quality traits in castor (Ricinus communis L.): GENE ACTION, HETEROSIS AND INBREEDING DEPRESSION IN CASTOR - M S PATEL; R M CHAUHAN (Journal of Oilseeds Research, 2013)
Gene action, heterosis and inbreeding depression study for yield and quality traits in castor (Ricinus communis L.) was carried out through six parameter generation mean analysis at Main Castor-Mustard Research Station, Sardarkrushinagar Dantiwada Agricultural University (SDAU), Sardarkrushinagar (SK Nagar). The experimental material included six families (P1, P2,F1,F2, BC1, BC2) of six crosses SH 72 x PRT 44, SKI 215 x SKI 166, PCS 124 x 37504, PCS 124 x JH 118, SKI 1 x JH 118 and HC 8 x JH 118. The charactersstudied were daysto flowering, daysto maturity,stemlength, number of nodes onmain stem, effective length of primary raceme, number of capsules on primary raceme, number of effective branches/plant, seed yield/plant, 100-seed weight, oil content in seed, endosperm content, oil content in endosperm, palmatic acid content, oleic acid content, linoleic acid content, linolenic acid content and ricinoleic acid content. The analysis of variance showed significant differences between all the generationsin majority ofthe characters ofthe crosses. The estimation ofscaling testsshowed that non-allelic interactions played an important role in the genetic control of all the characters. All the generations differed significantly for their mean(m) performance of all the traits. The estimates of gene effectsrevealed that both additive and non-additive gene actions were important for days to flowering, days to maturity, stem length, number of nodes on main stem, effective length of primary raceme, number of capsules on primary raceme, number of effective branches/plant, endosperm content, 100-seed weight, seed yield/plant, oil content in seed, linoleic acid content, linolenic acid content and ricinoleic acid content. Whereas, non-additive as well as epistatic gene actions were important for oil content in endosperm, palmatic acid content and oleic acid content. Crosses showing low heterobeltiosis effects also displayed high inbreeding depression for seed yield/plant in general. Utilization of biparental mating and reciprocal recurrent selection schemes which has the virtue of effectively exploiting, both additive and non-additive components, was suggested for exploiting present set of materials for obtaining high yielding genotypes of castor.